Multiplexing of reverse-transcription polymerase chain reaction for Hepatitis C virus genotyping - Hamzah, Hairul Aini; Mustafa Mahmoud, Mohammed Imad Al-Deen; Talib, Norlelawati A. (2013)
Background: Hepatitis C genotyping is a mandatory for the treatment and management of patients who are advised for interferon therapy. The gold standard of HCV genotyping is based on reverse-transcription polymerase chain reaction (RT-PCR), followed by DNA sequencing. Objective: We improved our two-tube format RT-PCR to one-tube for the HCV cDNA amplification. We also optimized the RT-PCR reaction for multiplexing purpose. Methodology: Two-tube assay was evaluated using a positive control with known HCV viral load (2,148,000 IU/ml), which was determined at Gribbles Laboratory (Australia). Optimization of one-tube format and multiplex RT-PCR were carried out using Superscript III One-Step RT-PCR System (Invitrogen, USA), targeting the universal 5’UTR and NS5B regions. Results: One-tube format was easily carried out using Superscript III One-Step RT-PCR System (Invitrogen, USA). However, multiplex system was not feasible with the optimized one-tube format. Multiplex RT-PCR was successfully performed with the undiluted HCV-RNA. The bands (414 bp & 212 bp) could be cut simultaneously for the gel extraction and purification using MinElute Gel purification System (Qiagen, Germany) prior to cDNA sequencing. HCV genotype 3, 1 and 4 could be determined by the assay but not HCV genotype 6. Conclusion: Since the majority of HCV strains in Malaysia are derived from the HCV genotype 3 and 1, this method can be used for rapid genotyping purposes.